Vioxx : too risky for Merck? - Petersen, Mitchell A.; Singhal, Rashmi (London : Kellogg School of Management, 2007)
The case outlines the poor decision making by executives of the pharmaceutical company Merck that resulted in its launching of the drug Vioxx and then stalling the withdrawal of the product. The student is invited to consider what caused executives and managers to make bad decisions and how these can be avoided in the future.
Originally published in Peterson, M. A., & Singhal, R. (2007). Vioxx: Too risky for Merck?. 5-207-253. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Merck-Medco (Firm); Vioxx; Drugs -- Safety measures